DEVELOPING WEB-BASED LEARNING MODEL BY COMBINING HOT POTATOES AND EDITPLUS TO OPTIMIZE THE INPUT IN ENGLISH LANGUAGE LEARNING - Yulina, Christina Atika (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
Technology, using its ability to reach audience at anytime and anywhere, has emerged as a powerful platform to assist learners in their language learning. This paper aims to discuss generally (1) how to develop web-based learning using Hot Potatoes and Editplus, and (2) how does web-based learning model using hot potatoes optimize English language learning. Krashen claims that real acquisition happens only as a result of exposure to comprehensible and meaningful input is only slightly beyond their current level of competence (i+1). Developing web-based learning model can be one of the strategy for providing comprehensible input for the learners since it can be accessed at anytime and anywhere by anyone. Besides, web-based learning model help the learners exposed by other platforms easily, leading them to unconscious daily input to English language. Little research discusses about the combination use of Hot Potatoes and Editplus in making a web-based learning. This paper discusses the detailed steps to build a web-based learning using HotPotatoes combined with Editplus, in order to make a web-based learning model to optimize the input in English language learning.Â